If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6*(6-5) = 66/11
1*6 = 6
6 = 6
L = P
| x+16=4x-7 | | 31=-.06m | | 29b^2+48-88b=0 | | Log[5](x-3)-log[5](x+4)=2 | | (6+3d)-3d=-10 | | 13(7x-8)=9x-6 | | 17x+48=180 | | -7(7x+5)-5= | | 31=-.06 | | 6(2v)= | | 3(4/9)-5y=1 | | (2/3)z=4(1/4) | | g(6)=-2x+4 | | 15x^2-12x-99=0 | | 11v+8=9v-18 | | 3a+4b=7b-a | | 17x+48=90 | | 4x^2+32x-64=0 | | 6=-7/2y | | 7a-4=4a+5 | | 4x^2+32-64=0 | | y/4=32 | | 23+30+x=90 | | 2(q-3)+6= | | 3-4(x+4)=6x-13 | | f(-2)=-8x-5 | | -6(n+3)+19=-2n-11 | | L=1/2pV^2SC | | 3.2+(h+5.1)= | | Y=(-1/5)-20-2 | | 45/B=15 | | -4-4s=-8-2s |